Comprehensive Health Insurance and access to maternal healthcare services among Peruvian women: a cross-sectional study using the 2021 national demographic survey - Eduardo Ramos Rosas; Volker Winkler; Luis Huicho; Magaly M. Blas; Stephan Brenner; Manuela De Allegri (BMC, 2023)
Abstract Background The government-subsidized health insurance scheme Seguro Integral de Salud ("SIS") was introduced in Peru initially to provide coverage to uninsured and poor pregnant women and children under five years old and was later extended to cover all uninsured members of the population following the Peruvian Plan Esencial de Aseguramiento Universal - "PEAS" (Essential UHC Package). Our study aimed to analyze the extent to which the introduction of SIS has increased equity in access and quality by comparing the utilization of maternal healthcare services among women with different insurance coverages. Methods Relying on the 2021 round of the nationally-representative survey "ENDES" (Encuesta Nacional Demográfica y de Salud Familiar), we analyzed data for 19,181 women aged 15-49 with a history of pregnancy in the five years preceding the survey date. We used a series of logistic regressions to explore the association between health insurance coverage (defined as No Insurance, SIS, or Standard Insurance) and a series of outcome variables measuring access to and quality of all services along the available maternal healthcare continuum. Results Only 46.5% of women across all insurance schemes reported having accessed effective ANC prevention. Findings from the adjusted logistic regression confirmed that insured women were more likely to have accessed ANC services compared with uninsured women. Our findings indicate that women in the "SIS" group were more likely to have accessed six ANC visits (aOR = 1.40; 95% CI 1.14-1.73) as well as effective ANC prevention (aOR = 1.32; 95% CI 1.17-1.48), ANC education (aOR = 1.59; 95% CI 1.41-1.80) and ANC screening (aOR = 1.46; 95% CI 1.27-1.69) during pregnancy, compared with women in the "Standard Insurance" group [aOR = 1.35 (95% CI 1.13-1.62), 1.22 (95% CI 1.04-1.42), 1.34 (95% CI 1.18-1.51) and 1.31(95% CI 1.15-1.49)] respectively. In addition, women in the "Standard Insurance" group were more likely to have received skilled attendance at birth (aOR = 2.17, 95% CI 1.33-3.55) compared with the women in the "SIS" insurance group (aOR = 2.12; 95% CI 1.41-3.17). Conclusions Our findings indicate the persistence of inequities in access to maternal healthcare services that manifest themselves not only in the reduced utilization among the uninsured, but also in the lower quality of service coverage that uninsured women received compared with women insured under "Standard Insurance" or "SIS". Further policy reforms are needed both to expand insurance coverage and to ensure that all women receive the same access to care irrespective of their specific insurance coverage.